Using silicon nanoparticles to modify the surface of graphene nanosheets. (1st March 2018) - Savadkoohi, Marzieh; Dorranian, Davoud; Solati, Elmira
Abstract: In this work, the synthesis and properties of the graphene/silicon nanocomposites as a function of volumetric ratio of Si nanoparticles and graphene nanosheets suspensions has been investigated experimentally. Firstly the silicon nanoparticles and graphene nanosheets suspensions were synthesized by pulsed laser ablation method with Q-switched Nd:YAG laser. Then the mixture samples with different volumetric ratio of the graphene and Si suspensions were irradiated with UV radiation. UV–Vis–NIR spectroscopy, X-ray diffraction, transmission electron microscopy, scanning electron microscopy, Raman spectrum, potential and dynamic light scattering, and photoluminescence spectra were used to characterize the ablation products and graphene/silicon nanocomposites produced by UV irradiation. Results confirmed the successful production of silicon nanoparticles and graphene nanosheets, and also formation of graphene/silicon nanocomposites. According to the results, with increasing the concentration of graphene nanosheets in the suspensions the surface morphology of the graphene/silicon nanocomposites was exfoliated. Zeta potential implies that the suspension of samples with higher concentration of graphene nanosheets is more stable.